Intellectual Footwear and Disinfectant Bucket (Eurasian Journal of Research, Development and Innovation, 2024)
In the article human beings needs come without one how many to amenities have bolga , disinfectant , foot temperature normalizing, in the leg unconscious smells lubricat , dust , oil and water impermeable modern nanotechnologies based on created smart leg clothes about info given